2022
DOI: 10.3389/fcvm.2022.829825
|View full text |Cite|
|
Sign up to set email alerts
|

Quantitative Evaluation of Post-stenotic Blood Flow Disturbance in Canine Femoral Artery Stenosis Model: An Early Experience With Vector Flow Imaging

Abstract: ObjectiveTo investigate the value of Vector Flow Imaging (V Flow) in the assessment of post-stenotic turbulence in the canine arterial stenosis model.Materials and MethodsCanine femoral artery stenosis models were established using ameroid constrictors in 12 beagle dogs. 50% and then 70% femoral artery stenoses were confirmed by selective femoral artery angiography. V Flow was used to measure femoral artery flow turbulence index (Tur) preoperatively as a baseline. After establishing of a 50% and then 70% steno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Plaque formation usually occurs in non-laminar regions ( 33 35 ). Tur values increase with the degree of blood flow disturbance and arterial stenosis ( 23 , 36 ). Low WSS or high oscillatory WSS affect the morphological structure and function of endothelial cells, as well as promote the formation of atherosclerosis ( 16 , 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plaque formation usually occurs in non-laminar regions ( 33 35 ). Tur values increase with the degree of blood flow disturbance and arterial stenosis ( 23 , 36 ). Low WSS or high oscillatory WSS affect the morphological structure and function of endothelial cells, as well as promote the formation of atherosclerosis ( 16 , 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…This could be the reason why the two parameters (WSS and Tur) are negatively correlated since both low WSS and non-laminar flow are related to atherosclerosis and plaque formation. A previous study ( 36 ) demonstrated that flows with Tur value < 1% can be considered laminar or nearly laminar flow. Another recent study ( 40 ) presented the Tur difference between common carotid artery and carotid bulb.…”
Section: Discussionmentioning
confidence: 99%
“…Other biomarkers of relevance, such as turbulence, can be derived from vector flow imaging 46 , 47 . This turbulence will be most noticeable after the ligation and will cause substantial out-of-view flow.…”
Section: Discussionmentioning
confidence: 99%
“…The canine femoral artery stenosis model creation has been described in our previous report. 19 Twelve beagle dogs aged 12-24 months were purchased from the Animal Experiment Centre of Nongnong (Beijing) Biotechnology Co. Ltd (Beijing, China). Preoperative duplex ultrasound scanning was performed to confirm that internal diameters of the canine femoral arteries were 3.0 ± 0.1 mm.…”
Section: Establishment Of Canine Femoral Artery Stenosis Modelmentioning
confidence: 99%